How to make energy efficiency labels more effective: insights from discrete choice experiments in Ghana and the Philippines - Kuhn, Sascha; Kutzner, Florian; Thøgersen, John (Energy research & social science, 2022)
Energy efficiency labels have become an important tool in promoting environmentally friendly products. This paper provides insights into how to enhance the impact of energy efficiency labels in middle-income countries. Discrete choice experiments were conducted in Ghana (N = 876) and the Philippines (N = 797), examining whether appealing to attitude functions (the goals served by attitudes) can increase the effectiveness of energy efficiency labels of air conditioners. Local energy efficiency labels were modified to include different functional appeals to the benefits of energy efficiency of an air conditioner. A latent class approach was used to observe heterogeneities among respondents with regard to product attributes and functional appeals. Overall, we find energy efficiency to be an important attribute, which is valued more by people with higher environmental concern and knowledge. In addition, the effect of energy efficiency labelling can be increased by appealing to immediate attitude functions, to social-adjustive benefits (in Ghana) and to the expression of environmental values (in the Philippines). Functional appeals to delayed monetary savings appear to reduce the label’s impact. Results call for using contextually adapted campaigns to maximize the impact of energy efficiency labelling.